2021
DOI: 10.17478/jegys.821700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of science camp for enhancing STEM skills of gifted young scientists

Abstract: Programs and educational practices that enable gifted students to conduct science activities and develop themselves in engineering fields are rapidly increasing in Malaysia. One of them is the science camp to improve STEM skills. This study investigates the effectiveness of science camp (Junior Science Camp) towards young children's understanding and knowledge about science. One hundred and three children aged four to six years old participated in the three-day camp. Mixed research model was used in this resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…We found that there were significant differences between gifted students who took part in the scientific activity and those who did not (in favor of gifted students who participated in the scientific activity) in terms of self-confidence, leadership and leadership responsibility. According to a recent study, researchers examined the effectiveness of a science camp to increase young gifted children's capacity to comprehend and understand science and based on their findings, the camp was effective in increasing the young children's knowledge about STEM areas and their understanding about science (Mohd Zahidi et al, 2021). In the differentiated model of giftedness and talent, Gagné (2000) explained giftedness as the potential that places an individual in the top 10% of peers his or her own age in a specific domain, whereas he elaborated that for these skills to be developed into talents, formal and informal learning processes are required.…”
Section: Discussionmentioning
confidence: 99%
“…We found that there were significant differences between gifted students who took part in the scientific activity and those who did not (in favor of gifted students who participated in the scientific activity) in terms of self-confidence, leadership and leadership responsibility. According to a recent study, researchers examined the effectiveness of a science camp to increase young gifted children's capacity to comprehend and understand science and based on their findings, the camp was effective in increasing the young children's knowledge about STEM areas and their understanding about science (Mohd Zahidi et al, 2021). In the differentiated model of giftedness and talent, Gagné (2000) explained giftedness as the potential that places an individual in the top 10% of peers his or her own age in a specific domain, whereas he elaborated that for these skills to be developed into talents, formal and informal learning processes are required.…”
Section: Discussionmentioning
confidence: 99%
“…They do not need to be taught like other normal children but are given the opportunity to learn on their own. Gifted students are said to like to learn systematically, to focus fully while the teacher is teaching in the classroom as well as diligently doing the exercises given by the teacher (Zahidi et al, 2021). Into the bargain, they learn easily, quickly and have high curiosity and are interested in high learning and academic achievement (Lv et al, 2019).…”
Section: Understanding the Gifted Traitsmentioning
confidence: 99%